Poslušanje kot učni cilj, vsebina in metoda v učbenikih za štiriletne srednje šole - Vogel, Jerica (Jezik in slovstvo, 2001)
Contemporary language teaching theory recognises communivative competence as the primary target in mother tongue teaching. As communication is a very broad concept including both production and reception of texts, there has been a growing demand to pay specific attention in mother tongue classes not only to writing, reading, and speaking but also to listening. In the past, listening and developing listening skills have been the most neglected aspects of communication both in theory and in practice. For that reason, this article first reviews contemporary psycholinguistic definition and presents some characteristics of this communicative activity. The second - central - part of the text then analyses Slovene secondary school textbooks to see how contemporary linguistic views have been finding their way into Slovene language teaching from 1970s on.
Keywords: didactic method; didaktika; jezikovni pouk; poslušanje; učbeniki; srednje šole